2007
DOI: 10.1152/japplphysiol.00067.2006
|View full text |Cite
|
Sign up to set email alerts
|

Muscle size, neuromuscular activation, and rapid force characteristics in elderly men and women: effects of unilateral long-term disuse due to hip-osteoarthritis

Abstract: Suetta C, Aagaard P, Magnusson SP, Andersen LL, Sipilä S, Rosted A, Jakobsen AK, Duus B, Kjaer M. Muscle size, neuromuscular activation, and rapid force characteristics in elderly men and women: effects of unilateral long-term disuse due to hip-osteoarthritis. J Appl Physiol 102: [942][943][944][945][946][947][948] 2007. First published November 22, 2006; doi:10.1152/japplphysiol.00067.2006.-Substantial evidence exists for the age-related decline in muscle strength and neural function, but the effect of long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
131
1
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(140 citation statements)
references
References 43 publications
5
131
1
3
Order By: Relevance
“…Hip OA has also been associated with significantly reduced lower limb muscle strength (39), however limited evidence is available to explain the role of hip and thigh musculature in the development and progression of the disease. Further research is required to explain this possible relationship.…”
Section: Muscle Strengthmentioning
confidence: 99%
“…Hip OA has also been associated with significantly reduced lower limb muscle strength (39), however limited evidence is available to explain the role of hip and thigh musculature in the development and progression of the disease. Further research is required to explain this possible relationship.…”
Section: Muscle Strengthmentioning
confidence: 99%
“…In humans, clinical studies have described joint conditions that are accompanied by inflammation [10][11][12] and that have been related to significant muscle changes, such as atrophy.…”
Section: Introductionmentioning
confidence: 99%
“…Although inflammatory joint conditions are common and clinical studies have shown morphological and functional alterations in the muscles related to injured joints 12,26,27 , the molecular mechanism related to the muscle adaptation to joint inflammation has not been studied to date. We hypothesized that joint inflammation induces molecular and structural changes in the soleus muscle related to the inflamed joint, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Muscle strength is partly determined by genetic factors 4 , but it is also highly dependent on muscle use 3,[5][6][7] . Inactivity decreases muscle strength, which often parallels a decrease in muscle mass 6,7 .…”
mentioning
confidence: 99%
“…Muscle strength is partly determined by genetic factors 4 , but it is also highly dependent on muscle use 3,[5][6][7] . Inactivity decreases muscle strength, which often parallels a decrease in muscle mass 6,7 . Pain [8][9][10] , disease 3,10,11 , and injury [12][13][14] have also been associated with a reduction in muscle strength and mass.…”
mentioning
confidence: 99%